2010
DOI: 10.1002/adfm.201001515
|View full text |Cite
|
Sign up to set email alerts
|

Description of the Morphology Dependent Charge Transport and Performance of Polymer:Fullerene Bulk Heterojunction Solar Cells

Abstract: We present a combined numerical charge transport and morphology model to describe the current density-voltage ( j -V ) characteristics of three different, benchmark polymer:fullerene bulk heterojunction organic solar cells in which the device performance critically depends on the processing conditions or composition of the active layer. We fi nd that an accurate description of the j -V characteristics over a broad bias range can be obtained when the actual complex, three-dimensional (3D) phase separation is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
83
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 34 publications
4
83
0
1
Order By: Relevance
“…The calculated current density, as shown in Fig. 4d, matches the experimental result using realistic parameters 39,42 . We also explicitly calculated the MFEs by assuming a change in the recombination mobility Dm r , or hole mobility Dm p .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The calculated current density, as shown in Fig. 4d, matches the experimental result using realistic parameters 39,42 . We also explicitly calculated the MFEs by assuming a change in the recombination mobility Dm r , or hole mobility Dm p .…”
Section: Discussionsupporting
confidence: 76%
“…Explicit simulations show that this can be traced back to the superposition of an almost constant and negative MC(V) due to the bipolaron mechanism (realized by a change in carrier mobility Dm p ) and a finite contribution from the e-h mechanism (change in recombination mobility Dm r ). The latter contribution is most probably related to the interaction of electrons and holes at the interface between the two phases in the blend, an effect which our device simulations take into account 39,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, the donor and acceptor materials should form interpenetrated networks of 10-20 nm-scale on account of the typical exciton diffusion length which is about 10 nm for conjugated polymers [4,5]. When represented by a two-dimensional model, it showed that a phase separated morphology with feature sizes smaller than ~50 nm could improve charge transport within and between the two phases and reduce bimolecular charge recombination [6]. In the case of P3HT/PCBM, the molecular ordering of rr-P3HT is concerned with photon absorption and hole transport [7][8][9], and the suitable size of phase separation is related to charge separation.…”
mentioning
confidence: 99%
“…Regioregular poly(3-hexyl-thiophene-2,5-diyl) (rr-P3HT) and fullerene derivative [6,6]-phenyl-C61-butyric acid methyl ester (PCBM) are respectively one of the most important donor and acceptor materials in polymer solar cells. The power conversion efficiency of devices based on them has been up to 5%-6% [1][2][3].…”
mentioning
confidence: 99%
See 1 more Smart Citation